How effective are interventions at reducing socioeconomic inequalities in obesity among children and adults? Two systematic reviews - Clare L Bambra; Frances C Hillier; Joanne-Marie Cairns; Adetayo Kasim; Helen J Moore; Carolyn D Summerbell (NIHR Journals Library, 2015)
Background: Tackling obesity is one of the major contemporary public health policy challenges and is vital in terms of addressing health inequalities. Objectives: To systematically review the effectiveness of interventions (individual, community and societal) in reducing socioeconomic inequalities in obesity among (1) children aged 0-18 years (including prenatal) and (2) adults aged ≥18 years, in any setting, in any country, and (3) to establish how such interventions are organised, implemented and delivered. Data sources: Nine electronic databases including MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO and NHS Economic Evaluation Database were searched from database start date to 10 October 2011 (child review) and to 11 October 2012 (adult review). We did not exclude papers on the basis of language, country or publication date. We supplemented these searches with website and grey literature searches. Review methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Experimental studies and observational studies with a duration of at least 12 weeks were included. The reviews considered strategies that might reduce existing inequalities in the prevalence of obesity [i.e. effective targeted interventions or universal interventions that work more effectively in low socioeconomic status (SES) groups] as well as those interventions that might prevent the development of inequalities in obesity (i.e. universal interventions that work equally along the SES gradient). Interventions that involved drugs or surgery and laboratory-based studies were excluded from the reviews. The initial screening of titles and abstracts was conducted by one reviewer with a random 10% of the sample checked by a second reviewer. Data extraction was conducted by one reviewer and independently checked by a second reviewer. The methodological quality of the included studies was appraised independently by two reviewers. Meta-analysis and narrative synthesis were conducted focusing on the 'best-available' evidence for each intervention type (defined in terms of study design and quality). Results: Of 56,967 papers of inequalities in obesity in children, 76 studies (85 papers) were included, and of 70,730 papers of inequalities in obesity in adults, 103 studies (103 papers) were included. These studies suggested that interventions that aim to prevent, reduce or manage obesity do not increase inequalities. For children, there was most evidence of effectiveness for targeted school-delivered, environmental and empowerment interventions. For adults, there was most evidence of effectiveness for primary care-delivered tailored weight loss and community-based weight loss interventions, at least in the short term among low-income women. There were few studies of appropriate design that could be included on societal-level interventions, a clear limitation of the evidence base found. Limitations: The reviews located few evaluations of societal-level interventions and this was probably because they included only experimental study designs. The quality assessment tool, although described as a tool for public health interventions, seemed to favour those that followed a more clinical model. The implementation tool was practical but enabled only a brief summary of implementation factors to be made. Most of the studies synthesised in the reviews were from outside the UK and related to women. Conclusions: The reviews have found some evidence of interventions with the potential to reduce SES inequalities in obesity and that obesity management interventions do not increase health inequalities. More experimental studies of the effectiveness and cost-effectiveness of interventions (particularly at the societal level) to reduce inequalities in obesity, particularly among adolescents and adult men in the UK, are needed. Study registration: The studies are registered as PROSPERO CRD42011001740 and CRD42013003612. Funding: The National Institute for Health Research Public Health Research programme.